2000
DOI: 10.1002/(sici)1097-0088(200001)20:1<47::aid-joc461>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

On the relationships between ENSO and autumn rainfall in Iran

Abstract: An investigation of the relationships between Iranian autumn rainfall and the El Niñ o -Southern Oscillation (ENSO) phenomenon was explored for the period . A negative correlation between the Troup Southern Oscillation Index (SOI) and rainfall data was found for almost all of Iran. The relationships were found to be stronger and more consistent over some regions comprising the southern foothills of the Alborz Mountains, northwestern districts and central areas. For the other parts of the country, correlations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 24 publications
5
47
0
Order By: Relevance
“…For autumn, the most effective drivers are DMI, AMO, and SOI with 20, 19, and 19 significant correlation coefficients, respectively. A connection between the interannual variation in Iranian precipitation and El Niño Southern Oscillation (ENSO) has been reported in several studies (e.g., Nazemosadat and Cordery, ; Nazemosadat and Ghasemi, ; Shirvani and Landman, ). Pourasghar et al .…”
Section: Resultsmentioning
confidence: 79%
“…For autumn, the most effective drivers are DMI, AMO, and SOI with 20, 19, and 19 significant correlation coefficients, respectively. A connection between the interannual variation in Iranian precipitation and El Niño Southern Oscillation (ENSO) has been reported in several studies (e.g., Nazemosadat and Cordery, ; Nazemosadat and Ghasemi, ; Shirvani and Landman, ). Pourasghar et al .…”
Section: Resultsmentioning
confidence: 79%
“…Yu et al [] attributed the interannual to decadal variability in Saudi Arabian dust activity to El Niño–Southern Oscillation (ENSO), sea surface temperatures (SSTs) in the tropical Indian Ocean and Mediterranean Sea, and North African rainfall and vegetation. ENSO's impact on Middle Eastern rainfall was previously demonstrated for the Arabian Peninsula [ Chakraborty et al , ; Tippett et al , ; Yu et al , ], Iran and Iraq [ Nazemosadat and Cordery , ; Mariotti , ; Zoljoodi and Didevarasl , ], Israel [ Price et al , ], and Kuwait [ Marcella and Eltahir , ], with drought typically associated with La Niña events. This ENSO‐rainfall relationship has intensified since the 1970s, potentially due to changes in the frequency and intensity of ENSO events and an apparent increased connectivity between the tropical Pacific Ocean and midlatitude circulations [ Wuethrich , ; Rajagopalan et al , ; Trenberth and Hoar , ; Price et al , ; Marcella and Eltahir , ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was found that the positive phase of NCP is associated with strong cyclonic activity over Iran, causing enhanced cloudy conditions and precipitation. Nazemosadat and Cordery (2000) found a negative correlation between the Southern Oscillation Index (SOI) and precipitation over most of Iran (cold phase of ENSO favours precipitation), particularly over the southern foothills of the Alborz Mountains, the northwestern and central areas. In addition, Nazemosadat and Ghasemi (2004) showed that warm ENSO events substantially reduce (increase) the intensity and probability of occurrence of dry (wet) periods during autumn, particularly over southern Iran.…”
Section: Introductionmentioning
confidence: 99%